Development of baseline stability in an electromagnetic flowmeter for dielectric liquids - Durcan, L. P. (Cranfield University, 1998)
This thesis is concerned with the development of a prototype electromagnetic flowmeter for dielectric liquids. A initial prototype flowmeter is tested in laboratory conditions with a liquid of low conductivity, the conclusion of these initial tests being that the stability of the flowmeter is below that required for its design applications. This lack of stability is a problem reported on several occasions in similar projects involving electromagnetic flowmeters for dielectric liquids. Therefore the main body of the work is spent investigating the causes of instability and trying to redress the necessary problems in order that a viable working prototype is developed. Problems of thermal instability, electrostatic and electromagnetic shielding are addressed along with the causes and effects of all the major noise and unwanted signals experienced in such a system. A new prototype is developed incorporating stability driven improvements. This new design is rigorously tested and assessed. The stability of the meter is considered with respect to its flow related output. Several parameters of operational stability are given in the examples considered. A final assessment is then made of the flowmeters baseline performance and a account of any remaining instability is given with respect to the issue developed throughout the thesis. The conclusions indicate that the electromagnetic flowmeter for dielectric fluids does produce a linear output based on Faraday's law of induction. They also indicate that the instability experienced previously can be broken into its constituent parts and each contributor accounted for and reduced, working towards the ideal totally stable flowmeter.